When Teamwork Works: Examining the Relationship Between Leader-Member Exchange Differentiation and Team Creativity - Du, Juan; Lin, Xinyue; Cai, Yahua; Sun, Fufu; Amankwah-Amoah, Joseph (Frontiers in Psychology, 2022)
Drawing on team creativity literature and social comparison theory, we investigate how leader-member exchange (LMX) differentiation influences team creativity. Using a survey based on 91 R&D teams from Chinese companies, we observe that LMX differentiation is negatively related to team creativity. More importantly, we demonstrate that team behavioral integration mediates the relationship between LMX differentiation and team creativity, and team emotional intelligence moderates the relationship between LMX differentiation and team behavioral integration. These results provide relevant suggests for organizational team building, management and development.